Start-ups, Venture Capitalists, and the Capital Gains Tax - Christian Keuschnigg; Søren Bo Nielsen (Center for Economic Studies and ifo Institute (CESifo), 2002)
A model of start-up finance with double moral hazard is proposed. Entrepreneurs have ideas but lack own resources as well as commercial experience. Venture capitalists provide start-up finance and managerial support. Both types of agents thus jointly contribute to the firm's success, but neither type's effort is verifiable. We find that the market equilibrium is biased towards inefficiently low venture capital support. In this situation, the capital gains tax is particularly harmful. The introduction of a small tax impairs managerial advice and leads to first order welfare losses. Once the tax is in place, limitations on loss off-set may paradoxically contribute to higher quality of venture capital backed entrepreneurship and welfare.
Keywords: 330; venture capital; capital gains taxation; double moral hazard.